Becoming a member of the police. Workplace expectations of police students during in-field training. Issue 1 (2nd January 2022) - Hoel, Linda; Dillern, Thomas
ABSTRACT: Research into workplace learning explores mostly the learner's perspective, which is also the case within police research. This paper focuses, instead, on police officers who have the role of field-training officers (FTO) and responsibility for presenting, teaching and guiding police students attending the higher education programme. The aim is to characterise the FTOs' expectations of the students as learners, and discuss how these expectations shape the professional development of the future police officers. Through analysis of interviews with the FTOs, we show how police socialisation is sedimented and perpetuated through situated learning in the workplace. The findings show that the FTOs' expectations can be characterised as opposites concerning students' participation in-house and participation on-patrol. In-house, the FTOs expected the students' participation to be passive, adaptive and obedient, while 'on-patrol' the FTOs expected that the students took a highly active role. The paper discusses how the social dimension of learning affects the police students' participation and progression into the police profession, and, in particular, the development their professional identity as future police officers who can contribute to, and further develop, police practice.